Role of the hypothalamic pituitary adrenal axis in the control of the response to stress and infection - McCann,S.M. (2000)
The release of adrenocorticotropin (ACTH) from the corticotrophs is controlled principally by vasopressin and corticotropin-releasing hormone (CRH). Oxytocin may augment the release of ACTH under certain conditions, whereas atrial natriuretic peptide acts as a corticotropin release-inhibiting factor to inhibit ACTH release by direct action on the pituitary. Glucocorticoids act on their receptors within the hypothalamus and anterior pituitary gland to suppress the release of vasopressin and CRH and the release of ACTH in response to these neuropeptides. CRH neurons in the paraventricular nucleus also project to the cerebral cortex and subcortical regions and to the locus ceruleus (LC) in the brain stem. Cortical influences via the limbic system and possibly the LC augment CRH release during emotional stress, whereas peripheral input by pain and other sensory impulses to the LC causes stimulation of the noradrenergic neurons located there that project their axons to the CRH neurons stimulating them by alpha-adrenergic receptors. A muscarinic cholinergic receptor is interposed between the alpha-receptors and nitric oxidergic interneurons which release nitric oxide that activates CRH release by activation of cyclic guanosine monophosphate, cyclooxygenase, lipoxygenase and epoxygenase. Vasopressin release during stress may be similarly mediated. Vasopressin augments the release of CRH from the hypothalamus and also augments the action of CRH on the pituitary. CRH exerts a positive ultrashort loop feedback to stimulate its own release during stress, possibly by stimulating the LC noradrenergic neurons whose axons project to the paraventricular nucleus to augment the release of CRH.